Effect of P nature phosphate dosage and embedding time of Azolla mycrophylla Kaulfuss on Yield of Rice (Oryza sativa L.) - Mahmudah Hamawi; Husni Thamrin Sebayang; Setyono Yudo Tyasmoro (Gontor AGROTECH Science Journal, 2016)
The effort of growing azolla in intercroping rice will be hoped to supply a green manure for rice plants. Additing P of the phosphat rock in the field can be expected to increase the result of rice yield.The research was conducted on December 2, 2006 to April 5, 2007 at Tegalgondo Karangploso of Malang. onsidering those problems, the researcher employs the factorial group randome desigh that compose two factor by controlling as comparison tool (inorganic treatment). The first factor is P in the phosphat rock contained 4 stages. As followed Po (without P), P1 (25 kg P ha-1), P2 (50 kg P ha-1), P3 (25 kg P ha-1). The second factor is time of incorporated Azolla microphylla Kaulfuss (W), which consist 4 stage. As followed W1 (incorporated 1 day before transplanting rice), W2 (50 % the azolla biomass in the field was incorporated during 14, 28, and 42 days after transplanting rice), W3 (50 % the azolla biomass in the field was incorporated during 21, and 49 days after transplanting rice), W4 (50 % the azolla biomass in the field was incorporated during 35 days after transplanting rice). The research was replicated 3 replications. The research finding showed that phosphat rock with 25 kg of P ha-1 doses combinationed with time of incorporating the azolla biomass at 14, 28 and 42 days after transplanting rice, the result of rice would be increasing in 31,4 % and R/C value resulted 1,47. Giving phosphat rock with 25 – 75 kg P ha-1 doses increased the azolla biomass at 146,4 % until 153 % and increased the yield of rice at 21,1% until 43,8 %.